2005
DOI: 10.1074/jbc.m507569200
|View full text |Cite
|
Sign up to set email alerts
|

Alg14 Recruits Alg13 to the Cytoplasmic Face of the Endoplasmic Reticulum to Form a Novel Bipartite UDP-N-acetylglucosamine Transferase Required for the Second Step of N-Linked Glycosylation

Abstract: N-linked glycosylation requires the synthesis of an evolutionarily conserved lipid-linked oligosaccharide (LLO) precursor that is essential for glycoprotein folding and stability. Despite intense research, several of the enzymes required for LLO synthesis have not yet been identified. Here we show that two poorly characterized yeast proteins known to be required for the synthesis of the LLO precursor, GlcNAc 2 -PP-dolichol, interact to form an unusual hetero-oligomeric UDP-GlcNAc transferase. Alg13 contains a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 37 publications
(31 reference statements)
4
109
0
1
Order By: Relevance
“…3A) agrees well with previous reports in which it was demonstrated that they associate with each other with high affinity to form a tight complex, using co-immuno-precipitation assays by ourselves (18) and pull-down assays by another group (19 (HIS3 and ADE2). Co-transformant cells expressing both bait and prey proteins were selected on synthetic dextrose (SD) minimal medium lacking leucine and tryptophan (SD-LW), then transferred onto SD medium lacking leucine, tryptophan, histidine (SD-LWH), and to SD medium lacking leucine, tryptophan, histidine, and adenine (SD-LWHA), and incubated at 30 ˚C for 3 days.…”
Section: C-1 Halg7p Halg14p and Halg13p Form A Gpt/nagt Complexsupporting
confidence: 82%
“…3A) agrees well with previous reports in which it was demonstrated that they associate with each other with high affinity to form a tight complex, using co-immuno-precipitation assays by ourselves (18) and pull-down assays by another group (19 (HIS3 and ADE2). Co-transformant cells expressing both bait and prey proteins were selected on synthetic dextrose (SD) minimal medium lacking leucine and tryptophan (SD-LW), then transferred onto SD medium lacking leucine, tryptophan, histidine (SD-LWH), and to SD medium lacking leucine, tryptophan, histidine, and adenine (SD-LWHA), and incubated at 30 ˚C for 3 days.…”
Section: C-1 Halg7p Halg14p and Halg13p Form A Gpt/nagt Complexsupporting
confidence: 82%
“…Plates were incubated for 4 days at 24°C. NPC biogenesis and lipid homeostasis luminal marker Kar2-mRFP-HDEL (Gao et al, 2005). Endogenously produced sterols showed similar localization, as revealed by staining with filipin (data not shown).…”
Section: Production Of Neutral Lipids Is Essential For Viability Of Bmentioning
confidence: 62%
“…These proteins function as a heterodimer to transfer the second, β1,4--GlcNAc--linked GlcNAc to Dol--PP--GlcNAc (Bickel et al 2005;Chantret et al 2005;Gao et al 2005). Soluble Alg13, assigned to GT Family 1, is the catalytic subunit and associates with membrane--spanning Alg14 at the cytosolic face of the ER membranes (Averbeck et al 2007;).…”
Section: Assembly and Transfer Of The Dol--pp--linked Precursor Oligomentioning
confidence: 99%
“…Assembly and transfer of the Dol-PP-linked precursor oligosaccharide: Steps on the cytoplasmic face of the ER membrane: These steps are (i) transfer of GlcNAc-1-P from UDP-GlcNAc to Dol-P by Alg7, the target of the N-glycosylation inhibitor tunicamycin (Barnes et al 1984), (ii) transfer of b1,4-GlcNAc from UDP-GlcNAc by heterodimeric Alg13/Alg14 (Bickel et al 2005;Chantret et al 2005;Gao et al 2005), (iii) transfer of a b1,4-linked Man by Alg1 (Couto et al 1984), (iv) successive transfer of an a1,3 and an a1,6 Man by Alg2 (O'Reilly et al 2006;Kämpf et al 2009), and (v) transfer of two a1,2-linked Man by Alg11 (Cipollo et al 2001;O'Reilly et al 2006;Absmanner et al 2010). These proteins act in higher-order complexes Noffz et al 2009;File S2).…”
Section: N-glycosylationmentioning
confidence: 99%